Experimental Research of Temperature Measurement Process Characteristics Using Thermocouples; AIP Conference Proceedings; Vol. 2212 : Thermophysical Basis of Energy Technologies (TBET 2019) - Yashutina O. S. Olga Sergeevna (2020, 2020)
Title screen